The Effectiveness of Corrective Feedback in Young Learners’ Interlanguage Development - Malaika Naqeeb (`, 2025)
This paper examines how corrective feedback helps in interlanguage development among the young learners of English as a foreign language. Based on the second language acquisition (SLA) theories, the study examines the influence of three kinds of feedback (explicit correction, recasts and elicitation) and another kind of feedback (metalinguistic cues) on the grammatical correctness, fluency, and general language development in the learners. The form of mixed-method approach was adapted involving both classroom observations, testing on the performance of learners, and interviews (semi-structured). The samples were young EFL students aged 913 who are enrolled in an English program in a public school. Quantitative results indicated that students that were on constant feedback on the errors improved greatly on their accuracy and structural control whereas the students that were provided with little feedback performed inefficiently. Qualitative data provided information on positive attitude to feedback held by learners with a number reporting that corrections developed their sensitivity to errors and fostered long-term recall. Learthers had varied preferences: some of them preferred to have their errors directly corrected, others thought that implicit feedback was less scary and more likely to encourage them to contribute. This paper affirms that corrective feedback is a highly crucial pedagogical instrument in the molding of the interlanguage as far as it is utilized in a balanced and learner-sensitive fashion. Among the implications of Krashen to language teachers is incorporation of a diverse range of feedback methods that are related to the development level of students, their proficiency level and their affective needs. Keywords: Corrective feedback, interlanguage developing, young learners, second language acquisition, explicit and implicit feedback